REAKTUALISASI AJARAN WALISONGO DALAM PENDIDIKAN ISLAM DI ERA PERUBAHAN - Rahmatullah, Rahmatullah; Subekti, Mohammad Yusuf Agung (Al Ulya: Jurnal Pendidikan Islam, 2023)
The roles, contributions and teachings of Wali Songo in spreading Islam can be a lesson and role model for educators in responding to the challenges of the times. Re-actualizing the role of Wali Songo is one of method that can be done. The purpose of this research is to describe the role and teachings of Wali Songo in Islamic education and to describe the reactualization of Wali Songo teachings in Islamic education. The research approach and method used to reveal the research objectives is literature review. The researcher sought, collected and critically analyzed data from several books, journals, documents, literature then summarized the results. The results of the study stated that first, the role and teachings of Wali Songo in Islamic education are facts and historical data that can be taken as ibrah and role models. Second, the re-actualization of Wali Songo teachings in Islamic education can be carried out by internalizing-syncretizing and informal-collaborating.